Comparative study on antioxidant and sensory properties of natto prepared using different brands of starter culture - Jia Ying, Mong (2024)
Antioxidant activity and sensory properties of natto placed great significance to consumers, which were influenced by the brands of natto starter. This study was to investigate the total phenolic, total flavonoid content, DPPH radical scavenging assay, reducing power assay and sensory profile of natto prepared using two different brands of starter cultures. The Chuan Xiu starter includes B. subtilis var. natto, Lactoplantibacillus plantarum and maltodextrin, while Kawashimaya starter only contains B. subtilis strain. Among the samples, natto prepared using Kawashimaya (16.6 mg GAE/100g) and Chuan Xiu (24.6 mg GAE/100g) starter cultures exhibited the highest TPC. Besides, natto prepared using Kawashimaya (3.70 mg QE/100g) starter culture had the highest TFC. In terms of DPPH radical scavenging activity, both natto prepared using Kawashimaya and Chuan Xiu starters demonstrated the lowest IC50 values of 52.69 mg/L and 69.28 mg/L, respectively, compared to 124.61 mg/L for soybean without starter culture. Furthermore, natto prepared using Kawashimaya (8.41 mg/L) and Chuan Xiu (6.21 mg/L) starters exhibited lower EC50 values in reducing power than soybean without starter culture (17.09 mg/L). Sensory evaluation revealed no significant differences (p > 0.05) in aroma, taste chewiness and overall acceptability. However, natto prepared using Kawashimaya starter received a lower score for appearance compared to control natto, whereas natto prepared using Kawashimaya starter showed lower stringiness score compared to both the Chuan Xiu starter and the control natto. In general, natto prepared using Kawashimaya and Chuan Xiu starter cultures has the potential to improve the antioxidant ability of natto.